2022
DOI: 10.47747/ijfr.v3i2.745
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Asset Structure, Firm Size, Profitability and Business Risk on Capital Structure in Companies Listed on the IDX

Abstract: This study aims to determine the effect of asset structure, firm size, profitability and business risk on capital structure in companies listed on the Indonesian Stock Exchange (IDX). The object of research is property, real estate and building construction employee. The type of research used is asosiatif research with secondary data. The population was 91 companies; the research sample used purposive sampling method that collected 20 samples of the companies with 2016-2020 of the study period. The technical a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
1
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 6 publications
(12 reference statements)
0
2
1
1
Order By: Relevance
“…The result however did not support Afinindy, Salim, and Ratnawati [5], but supported the study result of Kartika, Fatimah, and Ladewi [6] which showed a significant relationship between firm size and profitability on long term debt.…”
Section: Resultscontrasting
confidence: 72%
See 2 more Smart Citations
“…The result however did not support Afinindy, Salim, and Ratnawati [5], but supported the study result of Kartika, Fatimah, and Ladewi [6] which showed a significant relationship between firm size and profitability on long term debt.…”
Section: Resultscontrasting
confidence: 72%
“…Although profitability has an impact on business value, it has no effect on capital structure. Kartika, Fatimah, and Ladewi [6] ascertained capital structure in businesses traded on the Indonesian Stock Exchange (IDX) is impacted by company size and profitability. Employees in the building, real estate, and property industries are the subject of the study.…”
Section: Empirical Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Maka (H4) yang menyatakan jika risiko bisnis membawa pengaruh negatif pada struktur modal ditolak atau terbukti. Temuan penelitian ini searah dengan penelitian yang Suadnyana & Wiagustini (2013), Andika & Fitria (2016), Sari (2016), Mustofa & Lestari (2021), dan Kartika et al, (2022) laksanakan yang mengungkapkan ditemukannya keterkaitan positif antara risiko bisnis dan struktur modal.…”
Section: Tabel 8 Hasil Uji F (Uji Simultan)unclassified